Fuel Economy Comparison between a Vehicle Having a Standard Power Train and a Vehicle Having Its Power Train Modified into a Hybrid with Cylinder Deactivation - Cabije, Tessie A.; Tuballa, Maria Lorena L.; Onia, Jaychris Georgette Y.; Ignacio, Roilo O.; Belloso, Telesforo M.; Belloso, Antonio L. (Silliman Journal, 2022)
Due in part to rising gas prices and concern over global warming, hybrid vehicles and vehicles with cylinder deactivation have been developed in order to improve automotive fuel efficiency. This study was an attempt at comparing the fuel economy of a vehicle with standard power train and another vehicle modified into a hybrid with cylinder deactivation. These vehicles currently make up less than 1% of vehicles worldwide. Success of this technology shows how some of the remaining 99% of vehicles may be made more fuel efficient.